Projeto e realização de controle fuzzy para manipulador industrial tipo SCARA e sua avaliação de desempenho à luz da norma ISO 9283 - Silva, José Leonardo Nunes da (2016)
This paper presents the retrofitting and evaluation of performance of an industrial manipulator SCARA. To achieve this objective was developed the mathematical modeling of the manipulator (Kinematics and Dynamics) and a theoretical study of the major controllers used in current industrial manipulators. The proposal controller of this paper is a controller of position based on fuzzy logic. A theoretical study of logic Fuzzy applied in robotics, controller design, development and stability analysis of the Fuzzy controller position is displayed. This controller is embedded in an industrial equipment PLC and SCADA system was developed to allow the operation and programming of the manipulator. Because it is an industrial manipulator performance evaluation was carried out in the ISO 9283 standard - "Manipulating Industrial Robots - Performance Criteria and Related Methods" used by manufacturers worldwide manufactures. Among the various criteria of the standard was adopted the accuracy of position and repeatability of position. The fuzzy controller presented as a result of their performance evaluation accuracy of 3.788 mm and position repeatability of 8.805 mm position. It is superior to conventional PID controller that presented accurate position 4.864 mm and repeatability position 13.232 mm. With the values of accuracy and repeatability presented the SCARA manipulator after retrofitting is able to execute tasks like parts manipulating, palletizing, steel foundry, collage, simple assembly and spot welding.